Islamic practices and small and medium enterprises performance: Is corporate social responsibility a missing link?. Issue 2 (14th September 2020) - Aziz, Yasir; Ullah, Rizwan; Mansor, Fadillah; Abdullah, Luqman Haji
Abstract : We examined the role of Islamic practices: Islamic work ethics, Islamic social finance, and religiosity in financial and environmental performances with corporate social responsibility (CSR) as a mediator. We collected data from 241 Pakistani enterprises through survey and applied structural equation modeling in AMOS. The results showed that Islamic work ethics and Islamic social finance have insignificant effects on financial performance but a significant influence on environmental performance. Religiosity has a significant effect on financial but an insignificant influence on environmental performance. Islamic practices significantly improve CSR activities in the SMEs, resulting in financial and environmental performances. Our research further showed that CSR partially mediates the effects of Islamic practices on financial and environmental performances. Top management of the SMEs is suggested to follow Islamic practices in order to configure their performance (financial and environmental). This research suggests policy implications for the policy makers to encourage Islamic practices in business dealing and trading in order to configure CSR and environmental practices.